Community Empowerment through Social Compass Strategy: Case Study of Empowerment in Processing Waste and Water Hyacinth - Ramadani, Rika Fitri; Heryanto, Nunu; Komar, Oong; Hasanah, Viena Rusmiati (Journal of Nonformal Education, 2020)
This research was motivated by the various empowerment strategies implemented in each community empowerment institution. Heterogeneous environmental conditions became a consideration in implementing empowerment strategies to the community. The empowerment strategy became the main capital to attract the attention of the community to take the empowerment program seriously. The purpose of this research was to describe the implementation of the empowerment strategies used at this institution. This research was conducted to analyze the social compass was applied. The research method used is qualitative using a case study approach. Data were collected through observation and interview technique. The informants consisted of three training program managers and three training participants. Data obtained then analyzed by procedures of data collecting, data reducing, data display, and conclusion. Result of this research indicated that applied social compass were resources, technology, knowledge, values, goals and felt needs, norms, positions and roles, power leadership and influence, sanctions, and space relations. The impact of this social compass strategy was changing in the social-economic structure of the community. The conclusion obtained from this study is that the applied social compass could create an independent community in looking for family livelihood and prosperity.